Can Citizen Scientists Contribute to Trail Assessment and Monitoring Programs? An Empirical Evaluation of Data Congruence and Overall Efficacy. - Cheung, Suet-Yi; Leung, Yu-Fai; Larson, Lincoln (Environmental Management, 2025)
Citizen science has been increasingly utilized for monitoring resource conditions and visitor use in protected areas. However, the quality of data provided by citizen scientists remains a major concern that hinders wider applications in protected area management. We evaluated a prototype, citizen science-based trail assessment and monitoring program in Hong Kong using an integrated evaluative approach with a specific focus on the congruence of data collected by trained volunteers and managers. Datasets were evaluated in two ways. First, we compared differences in average values and standard deviations for measured trail indicators across all 30 sampling points. Second, we explored how result patterns characterized by the coefficients of variation and statistical significance differed for data collected by managers and volunteers at each sampling point or trail feature. Results revealed that the two trail assessment methods (one by volunteers, the other by managers) yielded incongruent data for some variables (e.g., trail width and maximum incision depth), but not others (e.g., Trail problems of erosions and multiple trail treads). Results of group interviews also revealed some possible factors that may have led to incongruent results, such as lack of experience and different perceptions between volunteers and managers in recognizing trail problems. While this study shows the potential value of citizen science-based monitoring programs, further steps are recommended to enhance the quality and usability of citizen science data to support effective trail monitoring and management.